Treatment-related fertility impairment in long-term female childhood, adolescent and young adult cancer survivors: investigating dose-effect relationships in a European case-control study (PanCareLIFE). Issue 6 (21st March 2021) - van den Berg, M H; van Dijk, M; Byrne, J; Berger, C; Dirksen, U; Winther, J F; Fossa, S D; Grabow, D; Grandage, V L; Haupt, R; van den Heuvel-Eibrink, M M; Kaiser, M; et al.
Abstract: STUDY QUESTION: Which chemotherapeutic agents and body site-specific radiation fields are dose-dependently associated with an increased risk of fertility impairment in long-term female childhood, adolescent and young adulthood (CAYA) cancer survivors? SUMMARY ANSWER: Busulfan, lower abdominal radiotherapy (RT) and total body irradiation (TBI) seem to be associated with fertility impairment at any dose, whereas gonadotoxicity of melphalan and procarbazine is suggested at medium/high (>140 mg/m 2 ) or high dose (>5600 mg/m 2 ) therapy, respectively. WHAT IS KNOWN ALREADY: Several treatment-related fertility deficits, as assessed by both self-reported outcomes and hormonal markers are known to occur following treatment of CAYA cancer. However, knowledge regarding precise dose-related estimates of these treatment-related risks are scarce. STUDY DESIGN, SIZE, DURATION: The current case–control study was nested within the PanCareLIFE cohort study. In total, 1332 CAYA survivors from 8 countries, 9 institutions and 11 cohorts, participated in and contributed data to the study. PARTICIPANTS/MATERIALS, SETTING, METHODS: All participants were female 5-year CAYA cancer survivors. In total, 450 cases (fertility impaired survivors) and 882 matched controls (not fertility impaired survivors) were included. Fertility impairment was defined using both questionnaire data (primary or secondary amenorrhea; use of artificial reproductive techniques; unfulfilled wish to conceive) and hormonal data (FSH and anti-Müllerian hormone (AMH)). Multivariable logistic regression models were used to investigate the effect of (i) alkylating agent exposure, and (ii) dose categories for individual chemotherapeutic agents and for RT-exposed body sites. MAIN RESULTS AND THE ROLE OF CHANCE: A positive dose–effect relationship between cyclophosphamide equivalent dose (CED) score and fertility impairment was found, with survivors with a CED score > 7121 mg/m 2 being at a significantly increased risk of fertility impairment (odds ratio (95% CI) = 2.6 (1.9–3.6) P  < 0.001). Moreover, cumulative dose variables of the following treatments were significantly associated with fertility impairment: busulfan, carmustine, cyclophosphamide, melphalan, procarbazine, lower abdominal RT and TBI. Busulfan, lower abdominal RT and TBI seem to be associated with fertility impairment at any dose, whereas gonadotoxicity of melphalan and procarbazine is suggested at medium/high (>140 mg/m 2 ) or high dose (>5600 mg/m 2 ) therapy, respectively. LIMITATIONS, REASONS FOR CAUTION: Our study may have been subject to selection bias since data from about half of the original base cohorts were available for the current study. This could impact the generalizability of our study results. WIDER IMPLICATIONS OF THE FINDINGS: We identified survivors at high risk for fertility impairment and, consequently, for a reduced or even absent reproductive life span. Both girls and young women who are about to start anti-cancer treatment, as well as adult female survivors, should be counselled about future parenthood and referred to a reproductive specialist for fertility preservation, if desired. STUDY FUNDING/COMPETING INTEREST(S): This study has received funding from the European Union's Seventh Framework Programme for research, technological development and demonstration under grant agreement no. 602030. There are no competing interests. TRIAL REGISTRATION NUMBER: n/a